Effect of age of seedlings and plant hormones on quality and bolting in onion (Allium cepa L.) (Indian Journal of Arid Horticulture, 2025)
In the present investigation the response of 6, 8 and 10 week old seedlings of onion cv. N-53 was studied along with foliar application of Cycocel (500 & 1000ppm), Ethephon (2000 & 2500ppm) and Paclobutrazol (1000 & 2000ppm) in factorial RBD replicated thrice during Rabi season of 2014-2015 at Division of Vegetable Science and Floriculture, SKUAST, Jammu. The results showed maximum equatorial diameter of bulbs (6.11cm) and TSS (9.63°B) in 8 week old seedlings. Minimum bolting was recorded in 8 week old seedlings (16.99%) which was statistically superior to 10 and 6 week old seedlings. Significantly higher days to first bolt was observed in 8 week old seedlings (99.71 days) over 10 and 6 week old seedlings (96.19 and 77.76 days), respectively. It is evident from the results; application of Paclobutrazol 2000ppm recorded the maximum equatorial diameter of bulbs (5.79cm) and TSS (9.49°B) along with lowest bolting (35.99%) up to 97.22 days after transplanting. Interactive results between seedling age and plant hormones showed maximum equatorial diameter of bulbs (6.80cm), TSS (11.50°B) and lowest bolting (9.64%) in the treatment having 8 week old seedlings with Paclobutrazol 2000 ppm (A,P,). Seedlings of 8 week old attained A (5.70%) and A grade (15.00%) bulbs recovered along with other marketable grades like B (45.00%) and C (28.00%). While the seedlings aged 6 and 10 week old could not attain bulbs of A and A grade bulbs. The storage studies also pointed out minimum rotting (72.20%) and total weight loss (70.00%) in this treatment.
Keywords: Onion; Seedling age; Plant hormones; Total soluble solids (TSS); Bolting